PENGARUH PENDEKATAN MATEMATIKA REALISTIK DAN BENTUK PORTOFOLIO TERHADAP KEMAMPUAN KONEKSI MATEMATIKA - Nadar, Nadar (Pascasarjna Universitas Negeri Jakarta, 2016)
Abstract:The purpose of this study is to determine the effect of learning approaches and form of portfolios to connection capability study math class V students in primary schools. The design of this study by 2 x 2 factorial sample consisted of 111 students. Data analysis techniques analysis of variance (ANOVA) two way.The results obtained are: 1) the ability to connect mathematics to the group of students who were given a mathematical approach realistic higher than the group of students who were given a learning approach directly, 2) the ability to connect mathematics to the group of students who were given a kind of portfolio to see higher than the group of students who were given type of portfolio documentation, 3) there is an interaction effect between teaching approaches and form of portfolios to the connection capabilities of mathematics, 4) groups of students by type of portfolio to see higher if taught using realistic approach mathematics rather than learning approach directly, 5) the group of students who were given kind portfolio of documentation higher if taught using learning approach directly rather than mathematical approach realistic, 6) in the process of learning to use a mathematical approach realistic mathematical studies of their results will be higher by the type of portfolio view rather than by type of portfolio documentation, 7) in the learning process using a direct approach to learning their math study results will be higher by portfolio type of documentation rather than by type of portfolio views.Keywords: Learning Approaches,FormOf Portfolios, Mathematics Connection Ability.Abtrak:Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pendekatan pembelajaran dan bentuk portofolio terhadap kemampuan koneksi matematika. Desain penelitian ini disain faktorial 2 x 2 sampel terdiri dari 111 siswa.Teknik analisis data varians (ANOVA) dua arah. Hasil penelitian diperoleh adalah: 1) kemampuan untuk menghubungkan matematika untuk kelompok siswa yang diberi pendekatan matematika realistik lebih tinggi daripada kelompok siswa yang diberi pendekatan pembelajaran langsung, 2) kemampuan untuk menghubungkan matematika dengan kelompok siswa yang diberikan semacam portofolio untuk melihat lebih tinggi daripada kelompok siswa yang diberi bentuk dokumentasi portofolio, 3) ada pengaruh interaksi antara pendekatan pengajaran dan bentuk portofolio dengan kemampuan koneksi matematika, 4) kelompok siswa berdasarkan bentuk portofolio untuk melihat lebih tinggi jika diajarkan menggunakan realistis pendekatan matematika daripada belajar pendekatan langsung, 5) kelompok siswa yang diberi portofolio bentuk dokumentasi yang lebih tinggi jika diajarkan menggunakan pendekatan pembelajaran langsung daripada pendekatan matematika realistik, 6) dalam proses belajar menggunakan pendekatan matematika studi matematika realistik dari hasil mereka akan lebih tinggi dengan bentuk tampilan portofolio bukan oleh bentuk dokumentasi portofolio, 7) dalam proses pembelajaran menggunakan pendekatan langsung ke belajar hasil studi matematika mereka akan lebih tinggi dari tipe portofolio dokumentasi bukan oleh bentuk tampilan portofolio.Kata kunci: Pendekatan Pembelajaran, Bentuk Portofolio, Kemampuan Koneksi Matematika.